تطوير تعليم الاستماع على أساس نظرية الترميز الثنائي لآلان بايفيو لدى طلاب الثاني عشر بالمدرسة سفينة الهدى - Nur Faizin (Study Program of Arabic Language Education (PBA), 2026)
Listening constitutes one of the core linguistic skills in the teaching of Arabic. Nevertheless, it has not yet received adequate pedagogical emphasis, particularly in terms of instructional focus, the depth of training activities, the quality of auditory input, and the diversity of instructional media. Field observations further revealed a noticeable gap between the pedagogical requirements of listening instruction and the instructional design implemented at Al-Hidayah Al-Faraj Higher School, especially with regard to the limited exposure of learners to authentic native Arabic speech. This study employed the Dual Coding Theory proposed by Allan Paivio as a theoretical framework for instructional development. The theory emphasizes the integration of verbal and visual systems in meaning construction and in the enhancement of comprehension and memory. The research adopted a Research and Development (R&D) methodology using the Four-D model, integrating both qualitative and quantitative approaches. Data were collected through documentation, pre-tests, and post-tests, and were subsequently analyzed both qualitatively and quantitatively using descriptive statistics and the Miles and Huberman analytical model. The findings indicate that the development of listening instruction was conducted systematically based on an analysis of learners’ actual needs. The listening unit was redesigned to be more contextual and learner-centered by integrating authentic audio recordings of native speakers with contextualized visual elements, thereby reflecting an effective application of Dual Coding Theory. In addition, the provision of QR-code–based digital access was found to enhance interactivity and accessibility. However, although learners’ responses to the developed materials did not demonstrate a statistically significant quantitative improvement in post-test scores compared with pre-test results, feedback from both teachers and students was positive in terms of motivation, acceptance, and ease of use. This suggests strong pedagogical effectiveness and clear affective engagement, with considerable potential to achieve deeper and more sustainable learning outcomes over the long term.